Youth Unemployment in the Caribbean - Parra-Torrado, Monica (World Bank, Washington, DC, 2014)
Global economic shocks coupled with natural disasters left most Caribbean countries with zero to negative growth and high unemployment rates. The Caribbean region was strongly affected by the last great financial crisis, which resulted in a regional average of zero economic growth in 2010. The purpose of this note is to evaluate the nature of youth unemployment in order to propose policy options to address it. It is organized in three sections. The first section describes the trends and patterns of total unemployment. The second section focuses on youth unemployment. The third and final section discusses policy considerations.